Concrete-Abstract Metaphor: Critical Investigation on Figurative Language in Ariana Grande Song Lyrics - Abel Apriliyanti; Ni Nyoman Deni Ariyaningsih (Universitas Islam Negeri Palopo, 2025)
Metaphor provides emotions as an important role in literary works. Especially for personal emotional experiences in a modern song lyric. This research highlights the use of concrete-to-abstract metaphor to represent emotional experiences in a song lyric. While most previous studies only focus on classifying the types of metaphor. This study fills the void by analyzing how concrete-to-abstract metaphors are used in a modern song lyric to express personal emotion. This study aims to learn deep understanding about figurative language by analyzing the concrete-to-abstract metaphors that are found in Ariana Grande song lyrics. This study used descriptive-qualitative methods to analyze the data based on theory that was used in semantics. The data were collected from three songs in Ariana Grande’s album entitled Eternal Sunshine. Data analysis utilized Knickerbocker and Renninger (1963) figurative language theory for the metaphor analysis and Stephen Ullman (1964) for the metaphor types analysis. The study shows lyrics using concrete-to-abstract metaphor. In addition, these findings can expand the understanding of the song writer’s characteristics. It is hoped that this study can be referenced in the study of music, language, literature, and enrich further understanding and appreciation about figurative language and metaphor in various modern music.